Development of a flexible strain sensor from graphite-treated fabric for smart applications - Alatrash, Nsreen; Tuhmaz, Ghazal; Saffour, Ziad (Al-Nahrain Journal for Engineering Sciences, 2026)
This research is based on developing a flexible strain sensor from graphite-treated fabric using knife coating technology. Three sensors were formed, differing in the number of coating layers (2, 4, 6). The results of studying their properties had shown that with increasing a number of coating layers, the electrical conductivity value of the treated samples increased, reaching a value of (21.8×10-3 S/cm). The treated layer was superficial, as the penetration of the coating into the structure did not increase significantly. It was also shown that the treatment did not affect the fabric properties such as hardness and tear strength. When studying the sensor's performance, it was found that the sensor's resistance value changes with the change in its bending angle. The change rate was higher for the six-layer sample, and the response time was shorter, faster (0.8s), than the other samples. Then, a working system was applied to the sensor to give a command to turn the LED on or off by bending the sensor and it showed good performance. This, in turn, confirms the effectiveness of applying this sensor in smart wearable textiles.